In silico analysis of plant phytochemicals against secreted aspartic proteinase enzyme of Candida albicans - S. S. Meenambiga, R. Venkataraghavan, R. Abhishek Biswal (Journal of Applied Pharmaceutical Science, 2018)
Candida albicans, a polymorphic fungal species of human microflora, is pathogenic and known to cause immense damage to the host organism which includes biofilm formation, oral and skin infections in immune deficient individuals. Secreted aspartic proteinase (SAP) enzyme plays a major role in promoting virulence to C. albicans, and thus could be established as a drug target for Candida infections. As a result, inhibiting the enzyme’s active center using phytochemicals would reduce the severity of the enzyme’s virulence. The present work focuses on the in silico analysis of about 15 plant phytochemicals against the SAP enzyme using the AutoDock 4.2.6 software. The docking results were found to be promising with emodin having the highest binding score of −6.44 kCal/mol followed by the isoflavonoid equol with the binding score of −6.29 kCal/mol. Thus, these bioactive compounds could be used as leads for drugs targeting SAP enzymes in treating resistant Candida infections.
Keywords: Candida albicans, secreted aspartic proteinase (SAP), phytochemicals, in silico, AutoDock.